Efficacy and Safety of Intravenous Ferric Carboxymaltose in Geriatric Inpatients at a German Tertiary University Teaching Hospital: A Retrospective Observational Cohort Study of Clinical Practice. (5th July 2015) - Bach, Matthias; Geisel, Tabea; Martin, Julia; Schulze, Bettina; Schaefer, Roland; Virgin, Garth; Stein, Juergen
Abstract : Current iron supplementation practice in geriatric patients is erratic and lacks evidence-based recommendations. Despite potential benefits in this population, intravenous iron supplementation is often withheld due to concerns regarding pharmacy expense, perceived safety issues, and doubts regarding efficacy in elderly patients. This retrospective, observational cohort study aimed to evaluate the safety and efficacy of intravenous ferric carboxymaltose (FCM, Ferinject) in patients aged >75 years with iron deficiency anaemia (IDA). Within a twelve-month data extraction period, the charts of 405 hospitalised patients aged 65–101 years were retrospectively analysed for IDA, defined according to WHO criteria for anaemia (haemoglobin: <13.0 g/dL (m)/<12.0 g/dL (f)) in conjunction with transferrin saturation <20%. Of 128 IDA patients screened, 51 (39.8%) received intravenous iron. 38 patient charts were analysed. Mean cumulative dose of intravenous FCM was 784.4 ± 271.7 mg iron (1–3 infusions). 18 patients (47%) fulfilled treatment response criteria (≥1.0 g/dL increase in haemoglobin between baseline and hospital discharge). AEs were mild/moderate, most commonly transient increases of liver enzymes ( n = 5/13.2%). AE incidence was comparable with that observed in patients <75 years. No serious AEs were observed. Ferric carboxymaltose was well tolerated and effective for correction of Hb levels and iron stores in this cohort of IDA patients aged over 75 years.